Cardiometabolic and Blood Glucose Factors in Merdeka, Gandus, Sei Selincah and Basuki Rahmat Palembang Health Centers - Dhanty Mukhlisa; Jason Liando; Helen; Wahyu Arfina Juwita (HM Publisher, 2021)
Indonesia is the fourth most populous country in the world. One third of all deaths in Indonesia are caused by cardiovascular and cardiometabolic diseases. We estimate this is related to gender, specific age and vascular risk factors and other modifiable risk factors, such as smoking, hypertension, diabetes, increased total cholesterol and overweight. This research is a cross sectional study. The study was conducted in four Palembang City Health Centers namely Sei Selincah Health Center, Merdeka Health Center, Basuki Rahmat Health Center and Gandus Health Center. The study data was taken consecutively for each adult patient who came for treatment at the puskesmas, met the inclusion criteria and agreed to participate in the study. The data that has been collected is then analyzed using SPSS 18.0 for Windows. In this study obtained cases of hypertension, diabetes mellitus, hypercholesterolemia in the four health centers period 30 October - 25 November 2017 as many as 200 respondents. Obtained cases of hypertension as many as 152 respondents (76%), cases of diabetes melitus as many as 73 respondents (36.5%) and hypercholesterolemia as many as 39 respondents (19.5%). In this study no association was found between Diabetes mellitus and hypertension and hypercholesterolemia. risk factors for sex, age, BMI and smokers are risk factors that influence hypertension, while risk factors for diabetes mellitus are, gender, age, and BMI. As for hypercholesterolemia, the only risk factor that influences education level.